Highly diluted bioactive compounds (CBADs) increase productive performance in Pacific oyster (Magallana gigas) seed during the nursery phase : Biostimulation with CBADs in oyster seeds - Mazon Suastegui, José Manuel (2025)
The effect of Highly Diluted Bioactive Compounds (CBADs) was evaluated during the nursery phase of Pacific oyster (Magallana gigas) juveniles, cultured in upwelling experimental units with recirculating water and food flow, supplied via aerosiphon. The evaluation variables were the growth responses in weight, volume, and shell area. The CBADs evaluated in the study were Similia® medicines authorized for human use by the Ministry of Health of Mexico: T1: CaS (Calcarea sulphurica 30C), T2: BaC (Baryta carbonica 30C), T3: FeP (Ferrum phosphoricum 30C), T4: HeS (Hepar sulphuris 30C), T5: ZiM (Zincum metallicum 30C), and a control treatment (C), consisting of distilled water. The treatments were added to the culture water once daily for thirty days. The results showed no evidence that CBADs improved the survival of M. gigas seeds, but were effective for growth, since FeP (T3) provided a significant increase in weight and volume, while BaC (T2) significantly increased the shell area of the juveniles. These findings support the concept of using CBADs to enhance performance in oyster seed production. Given the differential effect of the CBADs, further studies are suggested to establish additive and synergistic combinations that optimize yield in oyster seed production.